Disturbance of mitochondrial functions provoked by the major long-chain 3-hydroxylated fatty acids accumulating in MTP and LCHAD deficiencies in skeletal muscle. (October 2016) - Cecatto, Cristiane; Godoy, Kálita dos Santos; da Silva, Janaína Camacho; Amaral, Alexandre Umpierrez; Wajner, Moacir
Abstract: The pathogenesis of the muscular symptoms and recurrent rhabdomyolysis that are commonly manifested in patients with mitochondrial trifunctional protein (MTP) and long-chain 3-hydroxy-acyl-CoA dehydrogenase (LCHAD) deficiencies is still unknown. In this study we investigated the effects of the major long-chain monocarboxylic 3-hydroxylated fatty acids (LCHFA) accumulating in these disorders, namely 3-hydroxytetradecanoic (3HTA) and 3-hydroxypalmitic (3HPA) acids, on important mitochondrial functions in rat skeletal muscle mitochondria. 3HTA and 3HPA markedly increased resting (state 4) and decreased ADP-stimulated (state 3) and CCCP-stimulated (uncoupled) respiration. 3HPA provoked similar effects in permeabilized skeletal muscle fibers, validating the results obtained in purified mitochondria. Furthermore, 3HTA and 3HPA markedly diminished mitochondrial membrane potential, NAD(P)H content and Ca 2+ retention capacity in Ca 2+ -loaded mitochondria. Mitochondrial permeability transition (mPT) induction probably underlie these effects since they were totally prevented by cyclosporin A and ADP. In contrast, the dicarboxylic analogue of 3HTA did not alter the tested parameters. Our data strongly indicate that 3HTA and 3HPA behave as metabolic inhibitors, uncouplers of oxidative phosphorylation and mPT inducers in skeletal muscle. It is proposed that these pathomechanisms disrupting mitochondrial homeostasis may be involved in the muscle alterations characteristic of MTP and LCHAD deficiencies. Highlights: 3-Hydroxy long-chain fatty acids (LCHFA) accumulate in LCHAD and MTP deficiencies. LCHFA disrupt energy and Ca + homeostasis in muscle mitochondria of young rats. LCHFA compromise respiration in skeletal muscle mitochondria and permeabilized fibers. 3HPA effects in muscle mitochondria cause mPT induction. These pathomechanisms may be involved in the muscle symptoms of these patients.